2012
DOI: 10.1111/j.1476-5381.2012.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction study of sulphasalazine in healthy subjects and the impact of curcumin as an in vivo inhibitor of BCRP

Abstract: BACKGROUND AND PURPOSEAn ATP-binding cassette (ABC) transporter, breast cancer resistance protein (BCRP)/ABCG2, limits oral bioavailability of sulphasalazine. Here we examined the effect of curcumin, the principal curcuminoid of turmeric, on oral bioavailability of microdoses and therapeutic doses of sulphasalazine in humans. EXPERIMENTAL APPROACHEffects of curcumin were measured on the ATP-dependent sulphasalazine uptake by hBCRP-expressing membrane vesicles and on oral bioavailability of sulphasalazine in wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
120
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 39 publications
6
120
1
Order By: Relevance
“…The study in question by Adkison et al (2010) used oral sulfasalazine enteric-coated tablets and, in fact, surprisingly showed no significant pharmacokinetic changes with oral coadministration of the BCRP inhibitor, pantoprazole, or a significant genedose effect of the BCRP 421 C.A functional polymorphism. These results stand in stark contrast to three independent clinical studies using oral immediate-release sulfasalazine tablets and/or suspension formulation, where significant 2-to 4-fold increases in sulfasalazine exposure were observed in carriers of the BCRP 421 C.A polymorphism and during coadministration of an oral BCRP inhibitor (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012), as well as three independent preclinical studies in Bcrp-knockout mice and rats (Zaher et al, 2006;Shukla et al, 2009;Zamek-Gliszczynski et al, 2012). As discussed by Adkison et al (2010), an accidental flaw in the execution of their study demonstrated the importance of proper formulation selection (suspension or immediate release, but not extended release), rather than disproving the utility of sulfasalazine as a marker of BCRP activity in humans.…”
contrasting
confidence: 53%
See 3 more Smart Citations
“…The study in question by Adkison et al (2010) used oral sulfasalazine enteric-coated tablets and, in fact, surprisingly showed no significant pharmacokinetic changes with oral coadministration of the BCRP inhibitor, pantoprazole, or a significant genedose effect of the BCRP 421 C.A functional polymorphism. These results stand in stark contrast to three independent clinical studies using oral immediate-release sulfasalazine tablets and/or suspension formulation, where significant 2-to 4-fold increases in sulfasalazine exposure were observed in carriers of the BCRP 421 C.A polymorphism and during coadministration of an oral BCRP inhibitor (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012), as well as three independent preclinical studies in Bcrp-knockout mice and rats (Zaher et al, 2006;Shukla et al, 2009;Zamek-Gliszczynski et al, 2012). As discussed by Adkison et al (2010), an accidental flaw in the execution of their study demonstrated the importance of proper formulation selection (suspension or immediate release, but not extended release), rather than disproving the utility of sulfasalazine as a marker of BCRP activity in humans.…”
contrasting
confidence: 53%
“…We would also like to comment on the authors' conclusion that sulfasalazine is not as sensitive to BCRP modulation in humans as knockout rodents based on the apparent discordance between the magnitude of oral sulfasalazine exposure increase in Bcrp-knockout rodent studies [23-to 111-fold (Zaher et al, 2006;Shukla et al, 2009;Zamek-Gliszczynski et al, 2012)] and that in human clinical studies [2-to 4-fold (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012)]. This difference in Bcrp function between complete genetic ablation in Abcg22/2 animals and partial Bcrp inhibition by gefitinib was also acknowledged in the original publication by Zaher Shukla et al (2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, resveratrol was reported to be affected by the BCRP efflux pump, hence limiting its bioavailability (Scheepens et al, 2010). Curcumin was advantageously reported to lower the expression of p-glycoprotein transporters, as well as inhibit BCRP transporters in vivo (Holland et al, 2006;Nabekura, 2010;Kusuhara et al, 2012), and hence, the combination of curcumin and resveratrol in the same formula is expected to have facilitated the brain delivery of resveratrol. As illustrated in Figure 6, the significantly lower amounts of the two drugs reaching the brain following intranasal administration of their aqueous solution could be ascribed to its rapid mucociliary clearance as well as its possible nasal drainage (Gabal et al, 2014).…”
Section: In Vivo Quantification Of the Two Polyphenols In The Brainmentioning
confidence: 99%